Passively Q-switched Yb:LuPO4 laser based on a coupled cavity with few-layer WSe2 acting as saturable absorber. (26th July 2018) - Dou, Xiaodan; Ma, Yanjun; Zhu, Min; Yi, Hongying; Xu, Honghao; Zhong, Degao; Teng, Bing; Yu, Haohai; Liu, Junhai
Abstract: We report on a passively Q-switched coupled-cavity Yb:LuPO4 laser oscillating at 1005–1020 nm with a sapphire based few-layer WSe2 serving as saturable absorber. With 12.2 W of pump power absorbed, an average output power of 3.32 W is produced at a repetition rate of 1.34 MHz with a slope efficiency of 38%; the resulting pulse energy, duration, and peak power are respectively 2.5 µ J, 28 ns, and 89.3 W. These results demonstrate the great potential of few-layer WSe2 for use as saturable absorber in developing multi-watt, high-repetition-rate, nanosecond passively Q-switched solid-state lasers in the 1 µ m spectral region.